Eye tracking analysis of minor details in films for audio description - Orero, Pilar; Vilaró, Anna (MonTi Monografías de Traducción e Interpretación, 2014)
This article focuses on the many instances when minute details found in feature films may have direct implications upon the development of both the visual and plot narratives. The main question we would like to ask examines whether very subtle details which may easily go unnoticed by the viewer should be audio described. To assess the visual consciousness of such minute details, a perception experiment was conducted using eye-tracking technology and questionnaires. Though the result is not conclusive, it shows a clear methodological approach in the field of the audio description of visual details, and does give some indication as to what should be taken into consideration in future studies and analysis. The article concludes by hinting at further tests and analyses which could be undertaken using eye-tracking technology.